Collagen Deposition Reduction by Vitamin E in Alcoholic Liver Injury - Noman Ullah Wazir, Farooq Khan, Nighat Ara, Ambereen Humayun, Nadeem Ullah Wazir, Saima Mumtaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Alcohol encourages fibrotic changes in liver by initiating collagen deposition in liver parenchyma. Vitamin E can slow down progress of fibrosis in alcoholic liver injury and play a defensive part against these changes. Aim To observe difference in fibrotic changes in livers of vitamin E treated and non-treated rabbits exposed to intra-gastric administration of alcohol. Study Design: Analytical experimental study Place and duration of study: Department of Anatomy, Peshawar Medical College, Peshawar Pakistan from 1st May 2019 to 30th October 2019. Methodology: Eighteen domestic type male rabbits (Oryctolaguscuniculus) were included. All animals were divided in two categories on the basis of experiment time frame. “Category E8” animals having 8 weeks’ time period and “Category E4” animals having 4 weeks experimental duration. Each category was then clustered in “Control Group A” (appropriate food as per standard laboratory requirements, and normal saline as drinking water was provided daily), “Experimental Group B” (proper standard nutrition, 30% solution of ethanol made in distal water in the dosage of 30ml per kg/day through nasogastric tube and normal saline for drinking purpose were provided daily) and “Experimental Group C” (treated with suitable standard required diet, 30% of ethanol solution made in distal water in the dosage of 30ml per kg/day via NG tube and “Vitamin E” 50mg dissolved in 2ml distal water per kg/day with same nasogastric tube daily and normal saline for drinking purpose were given). Results: Collagen fibers deposition (fibrosis) in liver stroma was detected and recorded according to Knodel histological activity index. Quantitative difference in the collagen deposition among all groups from both “Category E4” and “Category E8” presented vastly significant “P” values. Conclusion: Alcohol can cause major fibrotic changes in “liver” even if it is consumed for the minor duration of 4 to 8 weeks, and these alterations can be minimised by the proper use of vitamin e through its “antioxidant effect”.